2009
DOI: 10.1177/0018720809359349
|View full text |Cite
|
Sign up to set email alerts
|

Delays and User Performance in Human-Computer-Network Interaction Tasks

Abstract: Appropriate user interface tools providing delay feedback information can help modify user expectations and delay tolerance. These tools are especially valuable when delay conditions exceed a few seconds or when task constraints and system demands are high. Interface designs for HCNI tasks should consider assistant-style presentations of delay feedback, information freshness, and network characteristics. Assistants should also gather awareness of user time constraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
(23 reference statements)
4
8
0
Order By: Relevance
“…Our results support the scientific evidence from a study conducted in 2006 that concluded that technology effectiveness is affected by task complexity factor [ 31 ]. Task numbers 1, 2, 7, 9, and 10 were very simple, such as open or close a functional button on the reporting map.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results support the scientific evidence from a study conducted in 2006 that concluded that technology effectiveness is affected by task complexity factor [ 31 ]. Task numbers 1, 2, 7, 9, and 10 were very simple, such as open or close a functional button on the reporting map.…”
Section: Discussionsupporting
confidence: 90%
“…From the TBE results ( Figure 5 ), we expected that in addition to the cognition and knowledge needed to accomplish these tasks, usability issues we discovered in this study might make these tasks even more complicated than the investigators thought. The ORE results supported previous literature’s findings that the efficiency is relatively associated with the complexity of these tasks [ 31 ].…”
Section: Discussionsupporting
confidence: 88%
“…More complex interactions will be perceived as continuous in time ranges from 2 to 5 s. At SRTs of 7 to 10 s, the user will begin to give up on the task if no feedback occurs. Likewise, more and more evidence suggests that the time a user is willing to wait for a task largely depends on a multitude of factors, such as the complexity of the task (Caldwell & Wang, 2009;Dabrowski & Munson, 2011); environmental factors, such as time pressure (Caldwell & Wang, 2009); and the expertise of the user (Caldwell, 2008).…”
Section: Srt Durationmentioning
confidence: 99%
“…Findings on the benefits of decreased variability cast doubt on the main focus on shortening SRTs to improve HCI. Users have been found to accept longer SRTs when they are predictable and accepted as reasonable (Caldwell & Wang, 2009). Focusing on variability as a means to heighten predictability may be a fruitful approach.…”
Section: Variability Of Srtsmentioning
confidence: 99%
“…Due to the popularity of computer and network among college students, the influences of network on college students are especially obvious. Network has become an indispensable part of college students' life [1]. Interpersonal relationship based on network is turned into a significant aspect of college students' interpersonal interaction.…”
Section: Introductionmentioning
confidence: 99%